Legal Analysis of Violent Acts by Police Officers in Handling Demonstrations in the South Labuhan Batu Jurisdiction - Raditya Firmansyah; Sriono Sriono; Wahyu Simon Tampubolon; Indra Kumalsari M (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The handling of demonstrations by the police often receives public scrutiny, particularly regarding acts of violence that violate human rights principles and positive legal regulations. This study aims to analyze the legal basis for the implementation of police actions in demonstrations and assess the limitations of the use of force based on Law Number 2 of 2002 concerning the Police, Regulation of the Chief of Police Number 1 of 2009 concerning the Use of Force, and Law Number 39 of 1999 concerning Human Rights. The study uses a normative juridical method with a statutory approach and case studies. The results show that acts of violence by officers in handling demonstrations generally occur due to deviations from Standard Operating Procedures (SOPs), a lack of professionalism, and weak internal oversight. The implementation of the principles of necessity, proportionality, and accountability is still not optimal. This study recommends strengthening oversight mechanisms, increasing human rights training, and internal reform of the National Police to prevent abuse of authority. Police officers who commit violence that does not comply with procedures can be subject to disciplinary sanctions, code of ethics, and criminal charges based on the Criminal Code. In cases of excessive violence against protesters or without a valid reason, officers can be charged with assault under the Criminal Code, which carries the threat of imprisonment and fines.